Berlin electropolis : shock, nerves, and German modernity - Killen, Andreas (Weimar and now, 2006)
Focusing on the key groups of railway personnel, soldiers, & telephone operators, Killen traces the emergence in the 1880s & then later decline of the belief that modernity caused nervous illness.